Enhancing Climate Resilience of Rain-Fed Potato Through Legume Intercropping and Silicon Application - Nyawade, Shadrack; Gitari, Harun I.; Karanja, Nancy N.; Gachene, Charles K. K.; Schulte-Geldermann, Elmar; Sharma, Kalpana; Parker, Monica L. (Frontiers in Sustainable Food Systems, 2020)
A large portion of sub-Saharan Africa is situated in belts of uncertain rainfall and are characterized by low soil fertility with limited capacity to adapt to and mitigate the impacts of climate change. A field study was conducted in the semi-humid potato-growing belt of Kenya to test the effect of legume intercropping and water soluble silicon (orthocilicic acid) on soil erosion, and use efficiency of light and water. Potato (Solanum tuberosum L.) was grown singly and intercropped with dolichos (Lablab purpureus L.) or hairy vetch (Vicia sativa L.). Each cropping system was subjected to granular water-soluble silicon (Si) amendment at two rates (2.5 kg Si ha-1 (+Si) vs 0 kg Si ha-1 (-Si)). Plants receiving Si maintained significantly higher (p < 0.05) percent relative leaf water content (62–89% vs 52–72% in controls) and exhibited higher concentrations of proline (1.99–2.91 vs 1–1.19 մmol g-1), soluble carbohydrates (28–59 vs 10–28 մmol g-1) and electrolyte conductance (1409–3903 vs 746–2307 mS cm-1). Legume intercropping enhanced groundcover establishment and reduced soil and nutrient losses by 45–80% compared with sole potato. Crop yields were 2–3 fold greater in intercropping relative to sole potato and were significantly greater in treatments subjected to Si application. Land equivalent ratios were above unity in intercropping but less than unity in sole potato, and were 8–20% increased by Si application. Use efficiency of water (5.99–9.09 Kg ha-1 m-3) and light (1.98–2.98 g MJ-1) were significantly greater under legume intercropping compared with sole potato (1.13–3.23 Kg ha-1 m-3 and 0.77–0.98 g MJ-1 respectively) and increased with Si application. Integrative use of Si and legume intercropping presents the smallholder farmers an opportunity to increase productivity of potato while enhancing resource use efficiency and soil fertility in the semi-humid tropics.